Overexpression of GmWRKY172 enhances cadmium tolerance in plants and reduces cadmium accumulation in soybean seeds - Xian, Peiqi; Yang, Yuan; Xiong, Chuwen; Guo, Zhibin; Alam, Intikhab; He, Zihang; Zhang, Yakun; Cai, Zhandong; Nian, Hai (Frontiers in Plant Science, 2023)
Introduction Cadmium (Cd) stress is a significant threat to soybean production, and enhancing Cd tolerance in soybean is the focus of this study. The WRKY transcription factor family is associated with abiotic stress response processes. In this study, we aimed to identify a Cd-responsive WRKY transcription factor GmWRKY172 from soybean and investigate its potential for enhancing Cd tolerance in soybean. Methods The characterization of GmWRKY172 involved analyzing its expression pattern, subcellular localization, and transcriptional activity. To assess the impact of GmWRKY172, transgenic Arabidopsis and soybean plants were generated and examined for their tolerance to Cd and Cd content in shoots. Additionally, transgenic soybean plants were evaluated for Cd translocation and various physiological stress indicators. RNA sequencing was performed to identify the potential biological pathways regulated by GmWRKY172. Results GmWRKY172 was significantly upregulated by Cd stress, highly expressed in leaves and flowers, and localized to the nucleus with transcriptional activity. Transgenic plants overexpressing GmWRKY172 showed enhanced Cd tolerance and reduced Cd content in shoots compared to WT. Lower Cd translocation from roots to shoots and seeds was also observed in transgenic soybean. Under Cd stress, transgenic soybean accumulated less malondialdehyde (MDA) and hydrogen peroxide (H2O2) than WT plants, with higher flavonoid and lignin contents, and peroxidase (POD) activity. RNA sequencing analysis revealed that many stress-related pathways were regulated by GmWRKY172 in transgenic soybean, including flavonoid biosynthesis, cell wall synthesis, and peroxidase activity. Discussion Our findings demonstrated that GmWRKY172 enhances Cd tolerance and reduces seed Cd accumulation in soybean by regulating multiple stress-related pathways, and could be a promising candidate for breeding Cd-tolerant and low Cd soybean varieties.